Open-source power outlet system for IoT-based smart homes - Dias, Tiago (2020)
This paper presents an open-source wireless Smart Power Outlet (SPO) system to improve the control and monitoring of household appliances in IoT-based smart homes. The system supports not only the most typical SPO functionalities, such as remote on/off control or real-time monitoring of the current consumption, but also other important functionalities, like programming of the power supply time schedule, automatic interruption of vampire currents, or prevention of electrocutions. Moreover, the devised system architecture allows to connect multiple SPOs, even with different capabilities, in an IEEE 802.15.4 Sub-1 GHz Personal Area Network (PAN). This network is managed by a Controller that also acts as a border router, providing remote access to the SPOs. A prof-of-concept prototype of the system has been implemented and tested. The considered SPO and Controller were based on Simple-Link Sub-1 GHz CC1310 wireless microcontrollers running the Contiki OS. The obtained results demonstrate the basic functionalities offered by the proposed open-source SPO and suggest that it can be used to make the next generation of homes smarter at lower costs.